New design approaches for future technological scenarios. Connections between present and future - Laura Anselmi; Marita Canina; Carmen Bruno; Davide Minighin (Agathón)
We are witnessing an exponential technological development adopting digital processes in all aspects of our life, and establishing a symbiotic connection between physical and virtual realities. Design has been able to maintain a connection between humanities and technologies in its identity, and through the Design Thinking (DT) approach it has provided companies with quick and effective answers. But when new problems and new necessities appear, DT needs to change. The article dwells on the will to implement the process of DT with Design Future (DF) to create a new tool able to manage non-linear future scenarios and face social challenges of the future in advance. The article presents two new methodological approaches born from this integration (DT/DF) with the related hypothetical processes to design medium and long-term future scenarios in different contexts.